Is in vivo analysis of urinary stone composition feasible?: evaluation of an experimental setup of a Raman system coupled to commercial lithotripsy laser fibers - Miernik, Arkadiusz; Rassweiler, Jens (World journal of urology, 2015)
Purpose: Raman spectroscopy allows immediate analysis of stone composition. In vivo stone analysis during endoscopic treatment may offer advantages concerning surgical strategy and metaphylaxis. Urinary stone components were evaluated utilizing an experimental setup of a Raman system coupled to commercial laser fibers. Methods: Samples of paracetamol (acetaminophen) and human urinary stones with known Raman spectra were analyzed using an experimental Raman system coupled to common commercial lithotripsy laser fibers (200 and 940 µm). Two different excitation lasers were used at wavelengths of 532 and 785 nm. Numerical aperture of the fibers, proportion of reflected light reaching the CCD chip, and integration times were calculated. Mathematical signal correction was performed. Results: Both the laser beam profile and the quality of light reflected by the specimens were impaired significantly when used with commercial fibers. Acquired spectra could no longer be assigned to a specific stone composition. Subsequent measurements revealed a strong intrinsic fluorescence of the fibers and poor light acquisition properties leading to a significant decrease in the Raman signal in comparison with a free-beam setup. This was true for both investigated fiber diameters and both wavelengths. Microscopic examination showed highly irregular fiber tip surfaces (both new and used fibers). Conclusions: Our results propose that laser excitation and light acquisition properties of commercial lithotripsy fibers impair detectable Raman signals significantly in a fiber-coupled setting. This study provides essential physical and technological information for the development of an advanced fiber-coupled system able to be used for immediate stone analysis during endoscopic stone therapy.